Intracellular bactericidal activity and action mechanism of MDP1 antimicrobial peptide against VRSA and MRSA in human endothelial cells - Dashtbin, Shirin; Razavi, Shabnam; Ganjali Koli, Mokhtar; Barneh, Farnoosh; Ekhtiari-Sadegh, Sarvenaz; Akbari, Reza; Irajian, Gholamreza; Pooshang Bagheri, Kamran (Frontiers in Microbiology, 2024)
Staphylococcus aureus is a prominent cause of postoperative infections, often persisting within host cells, leading to chronic infections. Conventional antibiotics struggle to eliminate intracellular S. aureus due to poor cell penetration. Antimicrobial peptides are a new hope for tackling intracellular bacteria. Accordingly, this study examines the antimicrobial peptide MDP1, derived from melittin, for its efficacy against intracellular S. aureus.In this study, the physiochemical properties (Prediction of three-dimensional structure, circular dichroism and helical wheel projection analysis) were investigated.Extracellular antibacterial activity and cytotoxicity of MDP1 were also assessed. The mechanism of interaction of MDP1 with S. aureus was evaluated by molecular dynamic simulation, atomic force and confocal microscopy. Bacterial internalization into an endothelial cell model was confirmed through culture and transmission electron microscopy. The effect of the peptide on intracellular bacteria was investigated by culture and epi-fluorescence microscopy.Results and discussion: 3D structural prediction proved the conformation of MDP1 as an α-helix peptide. Helical-wheel projection analysis indicated the proper orientation of hydrophobic amino acid residues for membrane interaction. CD spectroscopy of MDP1 showed that MDP1 in SDS 10 and 30 mM adopted 87 and 91 % helical conformation.Atomic force and confocal microscopy assessments as well as molecular dynamics studies revealed the peptide-bacterial membrane interaction. MDP1, at the concentration of 0.32 µg mL -1 , demonstrated a fold reduction of 21.7 ± 1.8, 1.7 ± 0.2, and 7.3 ± 0.8 in intracellular bacterial load for ATCC, VRSA, and MRSA, respectively. Molecular dynamics results demonstrate a preferential interaction of MDP1 with POPG/POPE membranes, primarily driven by electrostatic forces and hydrogen bonding. In POPC systems, two out of four MDP1 interacted effectively, while all four MDP1 engaged with POPG/POPE membranes.Gathering all data together, MDP1 is efficacious in the reduction of intracellular VRSA and MRSA proved by culture and epi-fluorescent microscopy although further studies should be performed to increase the intracellular activity of MDP1.